2020
DOI: 10.1001/jamanetworkopen.2020.27472
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of Unawareness of Memory Decline in Individuals With Autosomal Dominant Alzheimer Disease

Abstract: Key Points Question How does lack of awareness (anosognosia) of memory impairment evolve in the Alzheimer disease (AD) trajectory? Findings In this cohort study of 2379 members of the Alzheimer’s Prevention Initiative Registry with a presenilin ( PSEN1 E280A) variant for autosomal dominant AD, awareness of memory function was increased in carriers and noncarriers approximately 14 years before their estimated median age of dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 59 publications
7
30
0
Order By: Relevance
“…Both the participants with low amyloid load and their study-partners reported more difficulties over time, resulting in stable ACD. A second longitudinal study (Vannini et al, 2020 ) selected 396 presenilin (PSEN1 E280A) variant carriers from the Colombia Alzheimer's Prevention Initiative Registry (Tariot et al, 2018 ), 59 of which were cognitively-impaired. ACD was measured as the subject-informant discrepancy on a memory complaint scale (Gatchel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Both the participants with low amyloid load and their study-partners reported more difficulties over time, resulting in stable ACD. A second longitudinal study (Vannini et al, 2020 ) selected 396 presenilin (PSEN1 E280A) variant carriers from the Colombia Alzheimer's Prevention Initiative Registry (Tariot et al, 2018 ), 59 of which were cognitively-impaired. ACD was measured as the subject-informant discrepancy on a memory complaint scale (Gatchel et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although anosognosia is very common at the clinical stage of AD, recent studies have shown that awareness starts to change even before the AD dementia stage (Folstein et al, 1975;Cacciamani et al, 2017Cacciamani et al, , 2020. Previous research has shown that some individuals may demonstrate heightened awareness of subtle cognitive changes at the preclinical stage, with a subsequent decline of awareness as the individual moves along the AD trajectory (Vannini et al, 2017a(Vannini et al, , 2020Hanseeuw et al, 2020). Additionally, recent studies have suggested that loss of awareness may be present in the predementia stages of AD, e.g., in the prodromal (Perrotin et al, 2015;Vannini et al, 2017c;Edmonds et al, 2018;Munro et al, 2018;Therriault et al, 2018) and even preclinical stages (Folstein et al, 1975;Cacciamani et al, 2017;Vannini et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, to date, three longitudinal studies have demonstrated that lack of awareness of memory impairment appears approximately 2 to 3 years before the clinical progression to AD diagnosis [ 24 ]. Of these studies, Wilson and colleagues [ 24 ] used the participant-objective discrepancy method, while Hanseeuw et al [ 5 ] and Vannini et al [ 25 ] used the participant-informant discrepancy. Despite these consistent findings, what is less clear is the mechanism underlying altered self-awareness across the AD spectrum (i.e., from the preclinical to the dementia stage), and especially any relationship between self-awareness and AD pathology.…”
Section: Introductionmentioning
confidence: 99%